Pengaruh Pendapatan Usaha, Beban Usaha, dan Bagi Hasil Pihak Ketiga terhadap Laba Usaha pada PT Bank Syariah Mandiri - Purnamasari, Laely (Winaya Mukti University, 2018)
The development of operating revenue in Syariah Mandiri Bank is quiet excellent along with the increasing awareness of Muslims in using Islamic banking services. However, the development of this revenue is not accompanied by proportional increase in net operating income. This article focuses on the discussion of the relationship of operating revenue, operating expense and profit sharing of third parties and their effects on net operating income at Syariah Mandiri Bank. The purposes of this research are to describe and analyze the relationship of operating revenue, operating expense and profit sharing of third parties and their effects on net operating income both partially and simultaneously. The research method used descriptive and verification. The results showed that the operating revenue and the operating expenses had a strong relationship with the third party profit sharing. For the results of the third parties, the operating revenue and the operating expenses partially were not proven to significantly affect the net operating income but the operating revenue and the operating expenses were proven to affect the net operating income significantly. From this research, it was also known that the operating revenue component that most influenced net operating income was the mudharabah income and the operating expenses that most influenced net operating income was the loss expense for the elimination of productive assets.